2020
DOI: 10.47536/jcrm.v21i1.203
|View full text |Cite
|
Sign up to set email alerts
|

A note on minke whales (Cetacea: Balaenopteridae) in Uruguay: strandings review

Abstract: The minke whale is the smallest of the living rorquals and is widely distributed in the tropical, temperate and polar waters of both hemispheres. In the western Southwest Atlantic Ocean there are two currently recognised species, the dwarf form of the common minke whale, Balaenoptera acutorostrata unnamed subsp. and the Antarctic minke whale B. bonaerensis. All stranding records and collected specimens of minke whale on the coast of Uruguay were reviewed and analysed. Between 1962 and 2018, 33 records were gat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 3 publications
0
3
0
Order By: Relevance
“…Besides stranding records of B. acutorostrata throughout the year, more juveniles and calves occur during the winter and spring in southern Brazil, as reported in a previous review of strandings on the east coast of South America (Milmann et al, 2020) and in Uruguay alone (Juri et al, 2020). The regional peak for neonates and immature individuals in northern Argentina is from March to July and Baldas & Castello (1986) suggested that this region is a nursery and birthing area.…”
Section: Discussionsupporting
confidence: 63%
“…Besides stranding records of B. acutorostrata throughout the year, more juveniles and calves occur during the winter and spring in southern Brazil, as reported in a previous review of strandings on the east coast of South America (Milmann et al, 2020) and in Uruguay alone (Juri et al, 2020). The regional peak for neonates and immature individuals in northern Argentina is from March to July and Baldas & Castello (1986) suggested that this region is a nursery and birthing area.…”
Section: Discussionsupporting
confidence: 63%
“…In the Southern hemisphere, dwarf common minke whales have been recorded in the Western South Atlantic (WSA) waters of Brazil, Uruguay, Chilean Patagonia and the Antarctic Convergence; in the Western South Pacific (WSP) waters of New Zealand, the northern Great Barrier Reef in Australia and the Antarctic Convergence, and in the Western Indian Ocean of Durban in South Africa (Baker 1983;Best 1985;Arnold et al 1997;Zerbini et al 1997;Capella et al 1999;Acevedo et al 2006;Siciliano et al 2011;Juri et al 2020;Milmann et al 2020). Pastene et al (2010) presented preliminary genetic evidences based on mtDNA of differentiation between WSA and WSP dwarf common minke whales.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, all cetacean species harboring this barnacle exploit, at least partially, waters within the 30°N-30°S belt [see 27 ]. In this context, Kasamatsu et al 11 inferred that breeding areas of Antarctic minke whales might be located between 5° and 30°S, and neonates and calves have been spotted within 2-34°S 18 , 19 , 33 , 130 – 132 . Accordingly, the detection of X. globicipitis could be a strong indication of minke whale stays in this latitude range, as some authors have previously suggested 24 , 25 , 35 , 125 , 129 .…”
Section: Discussionmentioning
confidence: 99%
“…Firstly, there are observations of Antarctic minke whales in the Southern Ocean all year round 14 16 , and at lower latitudes during the austral summer (e.g. Brazil, South Africa, Uruguay) 10 , 17 , 18 . Secondly, the arrival time to putative wintering and feeding grounds is variable and seems to depend on age and reproductive condition 19 .…”
Section: Introductionmentioning
confidence: 99%